PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA DENGAN MEDIASI KOMITMEN ORGANISASIONAL - Supriyani, Titik (Students Journal of Economic and Management, 2012)
The purpose of this study to determine the effect of principal leadership on organizational commitment and teacher performance, motivation against organizational commitment and teacher performance, organizational commitment against a teachers performance, the indirect effect of principal leadership and teacher motivation on performance mediated by organizational commitment. Location of research conducted in the State junior secondary school in Pati regency. in 2012. The number of samples in this study were 105 respondents and included the study population or census. The method is a qualitative and quantitative analysis. Quantitative analysis performed using multiple regression test with hypothesis testing set at the 5% significance level. To analyze the models with SPSS 16.0. The results showed that the direct leadership of the principal effect of 0139 on the performance of teachers and 0.438 for organizational commitment, motivation affect the performance of teachers by 0.323 and by 0.585 the organizational commitment, commitment or-ganisasional effect of 0.570 on teacher performance. Indirectly affect the principals leadership for 0.250 on teacher performance, while the motivation for 0.333 affect the performance of teachers organizational commitment mediated. The results of this study can be used by subsequent researchers as research material in the field of organizational behavior science or science like. Keywords: Â principal leadership, motivation, commitment organisasional and teacher performance